A Hybrid MMC-based induction motor drive with no torque restrictions at low speeds - Soto Sanchez, Diego Enrique; Reyes, Luis; Cardenas, Roberto (My University, 2021)
The adjustment of the DC-link voltage in proportion to the speed, except at very-low frequencies, can potentially overcome torque limitations in MMC-based AC motor drives. However, the grid- and motor-side converter require be equipped with FB cells. To reduce this requirement, this work proposes the use of Hybrid MMC converters. To further improve performance at very-low frequencies, it is proposed that the intermediate link, between the grid- and motor-side converter, be operated as AC link, instead of DC-link, but only at low speed. An AC link voltage having a relatively small amplitude and frequency, compared to nominal values of the motor, is sufficient to maintain the ripple as low as that of the nominal speed. Results shows that 50% and 25%, of the total number of cells in the grid- and motor-side converter, respectively, are required to be of the FB type. This may be a practical solution for medium power drives that require to operate at very-low frequencies without torque restrictions.
Keywords: induction motor drive; hybrid converter; modular multilevel converter